Adipokine Leptin Co-operates With Mechanosensitive Ca2 +-Channels and Triggers Actomyosin-Mediated Motility of Breast Epithelial Cells - Acheva, Anna; Kärki, Tytti; Schaible, Niccole; Krishnan, Ramaswamy; Tojkander, Sari (Frontiers in Cell and Developmental Biology, 2021)
In postmenopausal women, a major risk factor for the development of breast cancer is obesity. In particular, the adipose tissue-derived adipokine leptin has been strongly linked to tumor cell proliferation, migration, and metastasis, but the underlying mechanisms remain unclear. Here we show that treatment of normal mammary epithelial cells with leptin induces EMT-like features characterized by higher cellular migration speeds, loss of structural ordering of 3D-mammo spheres, and enhancement of epithelial traction forces. Mechanistically, leptin triggers the phosphorylation of myosin light chain kinase-2 (MLC-2) through the interdependent activity of leptin receptor and Ca2+ channels. These data provide evidence that leptin-activated leptin receptors, in co-operation with mechanosensitive Ca2+ channels, play a role in the development of breast carcinomas through the regulation of actomyosin dynamics.